1998
DOI: 10.1126/science.280.5365.918
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the AKT1 Potassium Channel in Plant Nutrition

Abstract: In plants, potassium serves an essential role as an osmoticum and charge carrier. Its uptake by roots occurs by poorly defined mechanisms. To determine the role of potassium channels in planta, we performed a reverse genetic screen and identified an Arabidopsis thaliana mutant in which the AKT1 channel gene was disrupted. Roots of this mutant lacked inward-rectifying potassium channels and displayed reduced potassium (rubidium-86) uptake. Compared with wild type, mutant plants grew poorly on media with a potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
497
4
11

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 648 publications
(528 citation statements)
references
References 18 publications
16
497
4
11
Order By: Relevance
“…How-Yi Wang et al 827 npg ever, little is known about the regulatory mechanism of these K + transporters. AKT1 has been identified as an important dual-affinity inward-rectifying K + channel participating in K + uptake from soil into cells in Arabidopsis roots [9][10][11][12]. More recently, we have demonstrated that AKT1 activity is positively regulated by a protein kinase AtCIPK23, and AtCIPK23 is in turn activated by AtCBL1 or AtCBL9 [13].…”
Section: Introductionmentioning
confidence: 74%
“…How-Yi Wang et al 827 npg ever, little is known about the regulatory mechanism of these K + transporters. AKT1 has been identified as an important dual-affinity inward-rectifying K + channel participating in K + uptake from soil into cells in Arabidopsis roots [9][10][11][12]. More recently, we have demonstrated that AKT1 activity is positively regulated by a protein kinase AtCIPK23, and AtCIPK23 is in turn activated by AtCBL1 or AtCBL9 [13].…”
Section: Introductionmentioning
confidence: 74%
“…This resting potential is set by the PM H + -ATPase and is normally kept close to the equilibrium potential for K + (Hirsch et al, 1998). Under salinity, the membrane depolarizes following the influx of positively charged Na + ions, which shifts membrane potential values above the equilibrium potential for K + and results in significant outward K + currents (Anschütz et al, 2014;Véry et al, 2014).…”
Section: Intrinsically Higher H + -Atpase Activity Is Essential To Comentioning
confidence: 99%
“…The negative membrane potential (-200 mV) within the plasma membrane in epidermal cells of roots (HIRSCH et al, 1998) provides a strong driving force for absorption of cations through secondary carriers. For example, the carriers of heavy metals in plants fall into four different families: as the CPx-ATPases, Nramps, CDF (facilitator of diffusion of cations), and ZIP, which are involved in the absorption of metals and homeostasis in general, playing a key role in tolerance to these elements (SETH, 2012).…”
Section: Absorption Transport and Plant Toxicity Of Heavy Metalsmentioning
confidence: 99%